2013
DOI: 10.1007/978-1-4614-7411-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Cerebral Oxygen Metabolism and Hemodynamics During ECPR with Hypothermia Measured by Near-Infrared Spectroscopy: A Pilot Study

Abstract: Increase of TOI during ECPR might reflect an improvement in cerebral blood flow, while decrease of TOI after ECPR might reflect oxygen utilization by the brain tissue as a result of neuronal cell survival. NIRS may be useful for monitoring cerebral hemodynamics and oxygen metabolism during CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…[24][25][26][27] Regional cerebral blood flow, most commonly represented by carotid blood flow or cerebral perfusion pressure, was found to have a strong correlation with cerebral oxygenation. 24,28,29 Similarly, coronary perfusion pressure, the most reliable indicator of myocardial perfusion, was found to correlate well with the ROSC and survival in both animal and clinical studies. [30][31][32][33][34][35] Given these findings, it was inferred that greater hemodynamic support in the setting of CPR could have significant incremental effects beyond standard ACLS treatment.…”
Section: Development Of Advanced Perfusion Strategiesmentioning
confidence: 79%
“…[24][25][26][27] Regional cerebral blood flow, most commonly represented by carotid blood flow or cerebral perfusion pressure, was found to have a strong correlation with cerebral oxygenation. 24,28,29 Similarly, coronary perfusion pressure, the most reliable indicator of myocardial perfusion, was found to correlate well with the ROSC and survival in both animal and clinical studies. [30][31][32][33][34][35] Given these findings, it was inferred that greater hemodynamic support in the setting of CPR could have significant incremental effects beyond standard ACLS treatment.…”
Section: Development Of Advanced Perfusion Strategiesmentioning
confidence: 79%
“…Two reports have shown a significant increase in the cerebral rSO 2 value after the application of ECPR in patients with OHCA; however, all of the reported patients had a poor neurological outcome or died [ 4 , 12 ]. One report showed that the tissue oxygen index decreased in a patient with a favourable neurological outcome ( n = 1) but that it did not change in patients with unfavourable neurological outcome ( n = 14) [ 13 ]. These reports also failed to show a relationship between the cerebral rSO 2 value during ECPR and the neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, we implemented ECPR in this case because the initial TOI was within the normal range ( 3 ). An initial regional cerebral oxygen saturation ≥40% predicts a favorable outcome in patients with CA ( 3 , 5 , 6 ). In our case, the TOI decreased just before ECPR implementation and increased to 55% immediately after that.…”
Section: Discussionmentioning
confidence: 99%
“…This higher TOI seemed to be caused by a decrease in the oxygen consumption of the injured neuronal cells and an increase in the oxygen carrying capacity due to ischemia-reperfusion. Yagi et al reported that a high initial TOI or continuously high TOI values during ECPR predict poor neurological outcomes ( 5 ). In the present case, the TOI values were not high but instead relatively low during the period after ECPR was discontinued, presumably because the oxygen consumption of the brain tissue was well-preserved.…”
Section: Discussionmentioning
confidence: 99%